A subcritical water extract of soil grown Zingiber officinale Roscoe: Comparative analysis of antioxidant and anti-inflammatory effects and evaluation of bioactive metabolites - Razak, Azraul Mumtazah; Zakaria, Siti Nor Asyikin; Abdul Sani, Nur Fathiah; Ab Rani, Nazirah; Hakimi, Nur Haleeda; Mohd Said, Mazlina; Tan, Jen Kit; Gan, Han Kwang; Mad Nordin, Mariam Firdhaus; Makpol, Suzana (Frontiers in Pharmacology, 2023)
Ginger (Zingiber officinale Roscoe) can scavenge free radicals, which cause oxidative damage and inflamm-ageing. This study aimed to evaluate the antioxidant and anti-inflammatory effects of soil ginger's sub-critical water extracts (SWE) on different ages of Sprague Dawley (SD) rats. The antioxidant properties and yield of SWE of soil- and soilless-grown ginger (soil ginger and soilless ginger will be used throughout the passage) were compared and evaluated. Soil ginger was found to yield 46% more extract than soilless ginger. While [6]-shogaol was more prevalent in soilless ginger, and [6]-gingerol concentration was higher in soil ginger (p<0.05). Interestingly, soil ginger exhibited higher antioxidant activities than soilless ginger by using 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assay. Subsequently, three (young), nine (adult), and twenty-one (old) months old SD rats were subjected to oral gavage treatments with either distilled water or the SWE of soil ginger at a concentration of 200 mg/kg body weight (BW) for three months. With ginger treatment, a reduced levels of tumour necrosis factor-α (TNF-α) and C-reactive protein (CRP) but not interleukin-6 (IL-6) were observed in young rats. In all ages of SD rats, ginger treatment boosted catalase activity while lowering malondialdehyde (MDA). Reduction of urine 15-isoprostane F2t in young rats, creatine kinase-MM (CK-MM) in adult and old rats and lipid peroxidation (LPO) in young and adult rats were also observed. The findings confirmed that the SWE of both soil and soilless grown ginger possessed antioxidant activities. Soil ginger produced a higher yield of extracts with a more prominent antioxidant activity. The SWE of soil ginger treatment on the different ages of SD rats ameliorates oxidative stress and inflammation responses. This could serve as the basis for developing a nutraceutical that can be used as a therapeutic intervention for ageing-related diseases.